We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
119
1
avatar

Find the asymptote of -4x^2 +y^2 -2y = 3 with a postive slope. Answer should be in y=mx+b form .

 

I was gettiing confused when trying to simplify the equation in to the equation of a hyperbola.

 Dec 8, 2018
 #1
avatar+100564 
+1

-4x^2 +y^2 -2y = 3      rewrite as

 

y^2 - 2y - 4x^2 = 3        complete the square on y

 

y^2 - 2y + 1 - 4x^2 = 3 + 1

 

(y - 1)^2  -   4x^2 =   4         divide both sides by 4

 

(y - 1)^2     -   x^2  

______         ____  =      1

   4                  1

 

In this form,   a = 2  , b = 1     h = 0    k = 1

 

The equation of the asymptote with the positive slope is 

 

y =  (a/b) ( x - h) + k        ....so...

 

y = (2/1) ( x - 0) + 1

 

y = 2x + 1

 

Here's the graph :   https://www.desmos.com/calculator/tenipf6zfq

 

 

 

cool cool cool

 Dec 8, 2018

9 Online Users

avatar
avatar
avatar
avatar